Awarenesss Triangle: Konsep Pengembangan Pendidikan Kristen bagi Generasi Tekno di Era Virtual - Carolina Etnasari Anjaya; Yonatan Alex Arifianto (Sekolah Tinggi Teologi Baptis, Jakarta, 2021)
The virtual era is now pushing for a style or life formation that corresponds to the world. This is contrary to the Christian faith which requires humans to let go of all the bonds of the world and focus on the Kingdom of Heaven. Because of this, the development of Christian education is very much needed as a means to change the way or formation of the life of the techno generation and all believers today to a lifestyle that is in accordance with the truth of God's word. This research method uses descriptive qualitative. The purpose of the research is to provide ideas for the development of Christian education in accordance with the current virtual era. The results of the research found that the development of Christian education Awareness Triangle or the triangle of awareness can be a development solution that suits the needs which include: first, the concept of self-awareness. Second, is the concept of visual awareness. Third, is the concept of mission awareness. The result of learning the Awareness Triangle is a style or life formation that is in accordance with Bible truth. AbstrakEra virtual saat ini mendorong kepada gaya atau formasi hidup yang berpadanan dengan dunia. Hal ini bertentangan dengan iman Kristen yang menuntut manusia untuk melepaskan segala ikatan dunia dan fokus kepada Kerajaan Surga. Oleh karena hal tersebut pengembangan pendidikan Kristen sangat dibutuhkan sebagai sarana untuk mengubahkan cara atau formasi hidup generasi tekno dan semua umat percaya saat ini kepada gaya hidup yang sesuai kebenaran firman Tuhan. Metode riset ini mempergunakan deskriptif kualitatif. Tujuan dari riset memberikan ide pengembangan pendidikan Kristen yang sesuai dengan era virtual saat ini. Hasil riset mene-mukan bahwa pengembangan pendidikan Kristen Awarenesss Triangleatau segitiga kesadaran dapat menjadi solusi pengembangan yang sesuai dengan kebutuhan yang meliputi: pertama, konsep kesadaran diri. Kedua, konsep kesadaran visi. Ketiga, konsep kesadaran misi. Hasil dari pembelajaran Awarenesss Triangle adalah gaya atau formasi hidup yang sesuai dengan kebenaran Alkitab.